2008
DOI: 10.1021/la8024952
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Anchored Poly(2-vinyl-4,4-dimethyl azlactone) Brushes as Templates for Enzyme Immobilization

Abstract: We explored surface-anchored poly(2-vinyl-4,4-dimethyl azlactone) (PVDMA) brushes as potential templates for protein immobilization. The brushes were grown using atom transfer radical polymerization from surface-anchored initiators and characterized by a combination of ellipsometry, atomic force microscopy, and X-ray photoelectron spectroscopy. RNase A was immobilized as a model enzyme through the nucleophilic attack of azlactone by the amine groups in the lysines located in the protein. The surface density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 49 publications
1
83
0
Order By: Relevance
“…Cullen et al used a poly(2-vinyl-4,4-dimethyl azlactone) (PVDMA) brush, which was covalently bonded to the enzyme RNase A to create a type of biosensor ( Figure 13) [174]. The bound RNase A retained up to 95% of the activity of the same concentration of free enzyme.…”
Section: Modification and Detection Of Biological Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cullen et al used a poly(2-vinyl-4,4-dimethyl azlactone) (PVDMA) brush, which was covalently bonded to the enzyme RNase A to create a type of biosensor ( Figure 13) [174]. The bound RNase A retained up to 95% of the activity of the same concentration of free enzyme.…”
Section: Modification and Detection Of Biological Componentsmentioning
confidence: 99%
“…Detection methods for biosensors include, micro-ring resonators [176], voltammetry [177][178][179], electrochemical detection [89,92,180], interferometric detection of scattering (iSCAT) [181], as well as secondary label methods such as ELISA [182] and fluorescence [174]. Methods such as fluorescence and ELISA can have a high degree of specificity and are amenable to microarray applications allowing detection of multiple components at once (Figure 14) [183,184].…”
Section: Modification and Detection Of Biological Componentsmentioning
confidence: 99%
“…Compared to many substrates such as nanoparticles, nanotubes and nanofiber templates have many advantages, including good mechanical and thermal properties, large surface area, easy handling and controllable porosity [9]. Three fundamental methods used for immobilization of proteins are epoxide ring opening, amidation and nitrilotriacetate complexation [10]. Epoxy groups are attractive among various chemical groups for biomolecule immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…The Rühe group [56] has polymerized n-methacryloyl-β-alanine succinimide ester from a surface-bound free radical initiator and demonstrated the functionalization of the activated ester with small molecules and oligomers with 80 nm polymer brushes. Cullen et al [57] used ATRP to grow polymer brushes of 2-vinyl-4,4-dimethyl azlactone on a surface to immobilize RNase A. They showed that the enzyme maintained activity while covalently attached to the polymer matrix.…”
Section: Introduction 355mentioning
confidence: 99%
“…They showed that the enzyme maintained activity while covalently attached to the polymer matrix. Polymer brushes bearing an azlactone group can also be quantitatively functionalized in aqueous environments without competitive hydrolysis [57][58][59].…”
Section: Introduction 355mentioning
confidence: 99%